PERENCANAAN CHECK DAM SUNGAI GLUGU KABUPATEN GROBOGAN, JAWA TENGAH - Abhibawa Tegar Kusuma; Deny Wijayanti; Pranoto Sapto Atmojo; Sutarto Edhisono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Glugu River is a tributary of the Lusi River under the authority of the Central River Region Pemali - Juana, precisely located in the administrative area of the Grobogan Regency. Location of Glugu River located upstream, gave effect to the degradation of the river channel, so as to stabilize the river flow necessary to design coservation structure on Glugu River, that is check dam.The data used for design check dam are the primary data (geotechnical, geometry Glugu River, and water when the flood elevation data) and secondary data (topographic maps and rainfall data). These data are used as a basis for planning the main dam, sub dam, apron, complement structure, stability control of structure, and as reference for determining the budget plan. From the calculation, the height of main dam is 5.00 m, the width spillway of main dam and sub dam are 41.00 m, the width crest of main dam is 2.50 m and the width crest of sub dam is 1.50 m, the upstream slope of the main dam and sub dam are 1 : 0.9, the downstream slope of the main dam and sub dam are 1 : 0.2, the width wing of main dam is 2.50 m and the width wing of sub dam is 1.50 m, the height of sub dam is 1.80 m, the length of apron is 17.87 m, the side of square -shaped drip holes are 0.5 m as 16 pieces. Check dam can accomodate 17112.29 m3of sediment and will be full for 1.27 years.The total cost to build the check dam of Glugu River is IDR 2,418,643,000.00 include VAT 10% and 210 days work construction.